Multi-Objective Mayfly Optimization in Phase Optimization of OFDM - Azeez, Abdul; Tarannum, Suraiya (IIUM engineering journal, 2023)
Communication systems have been used tremendously in recent years which results in the need for high data transmission rates. Orthogonal Frequency Division Multiplexing (OFDM) provides robust performance in frequency selective fading due to high bandwidth efficiency and inter-symbol interference. Various optimization techniques were applied in existing research to increase the efficiency of OFDM in a communication system. The existing research has a limitation of considering a single objective to improve the efficiency of OFDM and also has a local optima trap. This research proposes a Multi-Objective Mayfly algorithm (MOMF) to consider multi-objective and provides a proper trade-off between exploration and exploitation. The Partial Transmit Sequence (PTS) is applied in the model to test the performance. The FFT sizes and modulation orders are varied to evaluate the performance of the MOMF technique in phase optimization. The MOMF technique effectively increases the performance of the model than other existing optimization techniques. The MOMF technique provides a non-dominated solution to escape from local optima trap. The MOMF model considers PAPR, BER, and SER in MIMO-OFDM system to increase the efficiency of the system. The exploration-exploitation trade-off helps to improve the convergence and overcome local optima trap. The MOMF in OFDM phase optimization was evaluated using BER, SER, and Peak-to-Average Power Ratio (PAPR) metrics. The MOMF method has PAPR of 3.95 dB and PSO-GWO method has 4.92 dB of PAPR. ABSTRAK: Sistem komunikasi telah digunakan secara meluas sejak beberapa tahun ini dan dapatan kajian menunjukkan keperluan pada kadar transmisi data yang tinggi. Pemultipleksan Bahagian Frekuensi Ortogon (OFDM) menyediakan prestasi berkesan dalam pemilihan pemudaran frekuensi berdasarkan keberkesanan lebar jalur tinggi dan gangguan antara-simbol. Pelbagai teknik optimum digunakan pada kajian sebelum ini bagi meningkatkan keberkesanan OFDM dalam sistem komunikasi. Kajian tersebut mempunyai kekurangan dalam memilih satu objektif bagi membaiki keberkesanan OFDM dan juga mempunyai perangkap optima setempat. Kajian ini mencadangkan algoritma Mayfly Objektif-Pelbagai (MOMF) bagi memilih objektif-pelbagai dan menyediakan keseimbangan yang wajar antara eksplorasi dan eksploitasi. Urutan Pancar Separa (PTS) telah digunakan dalam model ini bagi menguji prestasi. Saiz FFT dan turutan modulasi dipelbagaikan bagi menguji keberkesanan teknik MOMF pada fasa pengoptimuman. Teknik MOMF dengan berkesan menaikkan prestasi model ini berbanding teknik-teknik sedia ada yang lain. Teknik MOMF menyediakan solusi kepada teknik bukan-dominasi bagi mengelak perangkap optima setempat. Model MOMF ini mengambil kira PAPR, BER, dan SER dalam sistem MIMO-OFDM bagi meningkatkan kecekapan sistem. Keseimbangan yang wajar antara eksplorasi-eksploitasi membantu dalam membaiki penumpuan dan mengatasi perangkap optima setempat. MOMF dalam fasa optimanisasi OFDM telah dinilai menggunakan BER, SER, dan matrik Nisbah Kuasa Puncak-kepada-Purata (PAPR). Kaedah MOMF mempunyai nilai PAPR sebanyak 3.95 dB dan kaedah PSO-GWO mempunyai PAPR 4.92 dB.